George Flies South - James, Simon (London Walker Books, 2011)
George does not feel ready to learn to fly, leave his nest, and go south with the other birds, despite his mother's encouragement, but when a strong autumn wind gets hold of the nest, he may have no choice.
Include Color Illustrations
Keywords: Animals--Infancy -- Flight -- Birds--Nests